2021
DOI: 10.3390/v13050830
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis D Virus and Hepatocellular Carcinoma

Abstract: Hepatitis D virus (HDV) is a small, defective RNA virus that depends on hepatitis B virus (HBV) for virion assembly and transmission. It replicates within the nucleus of hepatocytes and interacts with several cellular proteins. Chronic hepatitis D is a severe and progressive disease, leading to cirrhosis in up to 80% of cases. A high proportion of patients die of liver decompensation or hepatocellular carcinoma (HCC), but the lack of large prospective studies has made it difficult to precisely define the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…A meta-analysis showed a significantly increased risk of HCC in patients with chronic HDV hepatitis (CHD), with a pooled OR of 1.28 (95% CI 1.05–1.57; I2 = 67.0%), which increased to 2.77 in the absence of heterogeneity for prospective cohort studies (95% CI 1.79–4.28; I2 = 0%), compared to HBV monoinfection [ 98 ]. Nonetheless, data on the genomic signature of HDV or on the levels of HDV replication into the tumor are still lacking [ 99 ]. In a study conducted in Caucasian patients with HDV-HCC, gene expression was performed comparing malignant and non-malignant hepatocytes, reporting a molecular profile, which suggest that the molecular signature of HDV-HCC is different from HBV-HCC [ 100 ].…”
Section: Impact Of Hdv Infection On Liver Disease and Hcc Developmentmentioning
confidence: 99%
“…A meta-analysis showed a significantly increased risk of HCC in patients with chronic HDV hepatitis (CHD), with a pooled OR of 1.28 (95% CI 1.05–1.57; I2 = 67.0%), which increased to 2.77 in the absence of heterogeneity for prospective cohort studies (95% CI 1.79–4.28; I2 = 0%), compared to HBV monoinfection [ 98 ]. Nonetheless, data on the genomic signature of HDV or on the levels of HDV replication into the tumor are still lacking [ 99 ]. In a study conducted in Caucasian patients with HDV-HCC, gene expression was performed comparing malignant and non-malignant hepatocytes, reporting a molecular profile, which suggest that the molecular signature of HDV-HCC is different from HBV-HCC [ 100 ].…”
Section: Impact Of Hdv Infection On Liver Disease and Hcc Developmentmentioning
confidence: 99%
“…In contrast, HCV infection and nonalcoholic fatty liver disease (NAFLD) are major risk factors associated with HCC in western countries [1,16]. Another infectious factor considered to augment the risk of developing HCC is represented by the Hepatitis D-delta virus (HDV), a hybrid virus that acts as a satellite of HBV by incorporating the HBV surface antigen (HBsAg) and infecting only the persons that present an infection with HBV [17]. In addition, exposure to the Aspergillus-derived aflatoxin, obesity, smoking, oral contraception use, and alcohol intake are primary risk factors contributing to liver carcinogenesis [15,18].…”
Section: General Aspects Of Hccmentioning
confidence: 99%
“…In particular, the signaling cascades activated by G-protein coupled receptors and receptor tyrosine kinases like EGFR, namely the mitogen-activated protein kinase (MAPK)/ERK (or Ras/Raf/MEK/ERK) and PI3K/AKT/mTOR pathways, have been identified to be involved in the oncogenic process [ 65 ]. Interestingly, numerous studies conducted on HBV-, HDV- and HCV-associated HCC have been unraveling how deregulation of these cellular pathways by viral proteins drives hepatocarcinogenesis (i.e., reviewed in [ 66 , 67 , 68 ]). Interestingly, several studies have identified tumorigenesis pathways to be deregulated by HEV infection.…”
Section: Putative Molecular Factors Involved In Hev-mediated Hcc—hallmarks Of Cancermentioning
confidence: 99%